Dialogue and representation - Oblak, Tanja (Javnost (Ljubljana), 2002)
The Internet in many ways changed our established conceptions not only about space, time, and access, but also about publicness, activity and interaction. The interplay of these changes is clearly expressed in the idea of electronic public sphere, which itself depends heavily on the working of the dominant forms of communication. But it should be posed as a question rather than simply assumed whether new possibilities for participatory opinion formation come from interactive qualities of the Internet alone. As argued in this paper, cyberspace is constituted not only by interactive communication, but also by the forms of representation that are more similar to the elements of so-called mediated publicness, which originate from the process of normalisation of cyberspace. By approaching these issues through the conceptual framework of dialogue and representation, it is possible to reduce the complexity of cyberspace and thus to engage in a systematic analysis of the existing realms of public and political action.
Keywords: communication; komuniciranje; sociologija komunikacij; množične komunikacije; računalniške komunikacije; komunikacijska tehnologija